EMOTIONS, LINGUISTIC LANDSCAPE AND LANGUAGE LEARNING - Wiśniewska, Danuta (Neofilolog, 2019)
Emotions are a significant part of our lives. The question of how to communicate emotions is especially important for individuals who, apart from speaking their mother tongue, speak another, either second or foreign language. Research shows that there are differences across languages in terms of the vocabulary of emotion, in the concepts underlying lexical items, in the degree of ease of expressing and describing emotions. Therefore, teaching emotion words is of vital importance for successful communication. One of the factors which may be conducive in eliciting emotions is teaching materials. The purpose of this paper is to address the problem of expressing emotions in a foreign language and suggest the use of linguistic landscape as one of possible sources of input for teaching/learning how to perceive and communicate emotions in a foreign language effectively.